Attitude of Veterinarians Toward Self-Informed Animal Owners Affects Shared Decision Making - Merle, Roswitha; Küper, Alina M. (Frontiers in Veterinary Science, 2021)
The aims of this study were to investigate the role of the veterinarian characteristics (e.g., age, gender, self-estimation, use of the internet), and their attitudes concerning animal owners seeking self-information. A particular focus was laid on any association between shared decision making (SDM), age and gender. In an online survey, 527 German veterinarians were asked about their attitude regarding SDM principles and their experiences with self-informed animal owners. The factors associated with veterinarians’ perception of SDM were investigated in a multivariable linear regression model. A recently published structural equation model (1) consolidated the application of SDM, empathic behavior, and veterinarians’ evaluation of self-education as latent factors. Interconnected questionnaire items were processed using an exploratory factor analysis to 11 interpretable factors. Veterinarians who assumed therapy failure was associated with themselves had significantly higher rates of SDM (p=0.002). In contrast, SDM was significantly lower (p=0.002) if they assumed that therapy failure was due to the animal’s owners. SDM was negatively associated with the perceived quality of the pet owners’ self-information (p<0.001) and if skepticism was perceived as the reason for seeking the self-information (p=0.001). Veterinarians who advised against self-information (p=0.006) and those who assumed that self-information of animal owners goes along with uncertainty (p=0.001) had low SDM values (p=0.006). Asking the animal owner for self-information (p=0.001), and recommendations of good information sources (p=0.022) were positively associated with SDM. Looking at the influence of age and gender on the application of SDM, older people and males rated higher. However, the evaluation of the latent factor SDM was based on the self-estimation of the participants. Assuming that younger women were less self-confident, we cannot exclude that young female participants self-evaluated their SDM skills lower than older male participants, although both groups would objectively have the same SDM level. Practitioners who have a positive attitude toward animal owners, who enjoy contact with animal owners and welcome their interest in further (self-)information, show empathic behavior, and have a positive attitude toward SDM are more likely to have better veterinarian-animal owner-relationships.